Performance of Renal Function Prediction Equations in a Group of Hospitalized Chronic Kidney Disease Patients - Islam, M Hafizul; Dutta, Pradip Kumar; Hoque, Mahmudul; Alam, ASM Towhidul (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: chronic kidney disease (CKD); creatimine clearance (CrCl); cock croft-gault (CG) formula; modification of diet in renal disease (MDRD) equation DOI: 10.3329/jcmcta.v21i1.7665 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):18-22